Paederia cruddasiana Prain: A New Distributional Record for Arunachal Pradesh, India - Balkrishna, Acharya; Joshi, Bhasker; Srivastava, Anupam; Shankar, Rama; Ansari, Aqib; Mishra, Rajesh Kumar; Kumar, Aashish; Sharma, Sangam; Kumar, Amit; Prajapati, Uday Bhan (Indian Forester, 2023)
No Abstract.